Beyond the Classroom: The Impact of a University-Based Civic Hackathon Addressing Homelessness. - Wilson, Jennifer; Bender, Kimberly; DeChants, Jonah (Journal of Social Work Education)
Stigma and prejudice are barriers to developing policies addressing homelessness. Awareness development, using civic hackathons, may be beneficial in reducing stigma and promoting policy while offering unique training to social work students. The current study explores the feasibility of hosting a university-based homelessness hackathon; associated changes in self-perceived knowledge, attitudes, beliefs, and investment in addressing homelessness; and development of innovative solutions. Participants (N=32) attended a 7-hour event, involving expert panels, rapid iteration, and solution pitches. Pre- and postevent surveys demonstrate changes in knowledge and attitudes related to homelessness as well as civic responsibility. The event was less successful in generating deployable solutions. Findings suggest the benefit of university-based hackathons to train social work students and offer considerations for implementing hackathons in educational settings.